Infarct size and free fatty acids in the early phase of acute myocardial infarction - Tansey, M J B (Division of Cardiology, 2018)
The management of acute myocardial infarction (AMI) has been improved by the realisation that the size of infarction can influence mortality (Sobel et al, 1972) and that the infarct size can be altered by subsequent therapy (Maroko et al, 1972). The identification of any factor which may have adverse effects on the ischaemic myocardium and which is amenable to treatment would therefore have important prognostic implications. Elevation of circulating free fatty acid (FFA) concentrations is a consistent feature (Kurien and Oliver, 1966; Oliver et al, 1968) of the profound, non-specific metabolic reaction associated with the onset of AMI (Opie, 1975). The FFA rise has been correlated with the development of arrhythmias (Oliver et al, 1968) after AMI, and with the severity of ischaemic damage (Oliver et al, 1968; Gupta et al, 1969; Russell & Oliver, 1978) on clinical grounds. The method of quantifying infarct size developed by Shell et al (1972) has provided a means of correlating the degree of metabolic disturbance with extent of myocardial damage, and of assessing the benefits of metabolic interventions. The purpose of the studies reported in this thesis was to examine in detail the FFA rise in the early phase of AMI and to correlate this rise with the development of arrhythmias and other complications of AMI and with enzymatically estimated infarct size, thus leading to a more rational approach to therapeutic interventions.